O lugar das ocupantes no mercado de trabalho de Santa Maria/RS em 2004 - Porto, Vanessa Almeida (2006)
This study is a work market analysis in Santa Maria/RS by reading work opportunity tables provided by SINE, published on Diário de Santa Maria official newspaper in 2004. The central focus is the data by which it may be possible to analyse how work market positions women and men in occupations which are historically defined as different work fields. Therefore, I have analysed the relations between Geography, gender, and work market. The review of the literature, as well as analyses of built data, is based on readings of Louro (1997), Scott (1995), Meyer (2003), Perrot (1998), Rossini (2002), among so many others who have inspired this study. For the empirical material, I have drawn upon a multimethodological strategy. When there were obstacles to conduct the study, I defined new frontiers for my study. Some were invited to come in, others came in without my permission, and others are underlying the construction of my analysis focus. The final mode of binding and analyses in relation to women s occupations in the work market in Santa Maria are provided in three focuses, with relations between gender and educational level, gender and social carers, and gender and qualifications, also allowing to show that it is possible to see that the city s history favours a plenty of economic activities and opportunities for women in the work market. With these focuses, I observed that opportunities to work remained on the same addresses, which enables the same division between genders. Opportunities to work are higher and of better quality for men. Women continue to be called for domestic-related occupations, even if today they have more opportunities than in the past. There is still gender separation that causes social, economic, and cultural divisions.